KAJIAN TEKNOLOGI PRODUKSI BIOGAS DARI SAMPAH BASAH RUMAH TANGGA - Mappiratu, Mappiratu; Sikanna, Rismawaty (Univ. Tadulako, 2013)
The investigation about study the biogas production Technology from household waste has been done. This research aims to determine the starter concentration, water and household waste ratio to produc highest biogas, and also to find the fermentation time produce biogas with hight rendement. It was reache by applying 5 levels of cow dung starter concentration and 5 levels of water and household waste ratio i.e 0%, 6,25%, 12,5%, 18,75% and 25% and 1:2, 1:2,5, 1:3, 1:3,5 and 1:4 (b/v) respectively. The fermentation time was 3 days. The result showed that the higher cow dung concentration the lower biogas production. The highis biogas production (971,4 mg/L) was found with 6,25% of the starter. The increasing water and household waste ratio would decreased biogas production, and the using of 1:3,5 and 1:4 didn?t produce any biogas. The highest biogas production was found with 1:2 of water/household ratio i.e (631.29 mg/L). the fermentation time which produce the highest biogas rendement was found with 1 day of fermentation time